ANALYTICAL METHODS FOR THE DETERMINATION OF POLYBROMINATED DIPHENYL ETHERS IN HUMAN MILK - SAGİROGLU, ALİ ASRAM and TEKKELİ, SERİFE EVRİM KEPEKCİ and ONAL, CEM and DİNCEL, DEMET and ONAL, ARMAGAN (Journal of the Chilean Chemical Society, 2020)
Polybrominated diphenyl ethers (PBDEs), which are used as flame retardants, are widely used additives so many different kind of materials that are consumed by public. Current researches reveal a significant increase in the levels of PBDEs in human biological fluids all around the world. According to International Agency for Research on Cancer (IARC), PBDEs are declarated as carcinogenic agents and additionally a considerable risks have been shown in animal studies such as liver damage, alteration of thyroid hormone levels, neurotoxicity and hazardous effects on development of fetus. Due to the simplicity of human exposure routes such as ingestion, inhalation or dermal contact, it gains high importance to quantify PBDEs in biological fluids. The exposure to PBDEs is critic aspecially during pregnancy, fetus development and infancy. Excretion of PBDEs in human milk is the focus area for researchers in recent years. In this study, we reviewed current methodologies for the determination of PBDEs in human milk including sample preparation step, analytical procedure, validation parameters and observed levels of PBDEs in human milk. Because of the high physico-chemical stability of PBDEs, they have long persistence in human body. Besides, they reside in the lipid fractions of tissues because of their hydrophobic characteristics. Human breast milk has high lipid level, so that it is a suitable matrix for the accumulation and determination of PBDEs. Polybrominated diphenyl ethers (PBDEs), which are used as flame retardants, are widely used additives so many different kind of materials that are consumed by public. Current researches reveal a significant increase in the levels of PBDEs in human biological fluids all around the world. According to International Agency for Research on Cancer (IARC), PBDEs are declarated as carcinogenic agents and additionally a considerable risks have been shown in animal studies such as liver damage, alteration of thyroid hormone levels, neurotoxicity and hazardous effects on development of fetus. Due to the simplicity of human exposure routes such as ingestion, inhalation or dermal contact, it gains high importance to quantify PBDEs in biological fluids. The exposure to PBDEs is critic aspecially during pregnancy, fetus development and infancy. Excretion of PBDEs in human milk is the focus area for researchers in recent years. In this study, we reviewed current methodologies for the determination of PBDEs in human milk including sample preparation step, analytical procedure, validation parameters and observed levels of PBDEs in human milk. Because of the high physico-chemical stability of PBDEs, they have long persistence in human body. Besides, they reside in the lipid fractions of tissues because of their hydrophobic characteristics. Human breast milk has high lipid level, so that it is a suitable matrix for the accumulation and determination of PBDEs.